(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to demonstrate the impact of preparing extended reports using brainstorming on the quality of auditing, and to present and analyze the role of using brainstorming sessions in raising the level of the extended auditor’s report and the quality of auditing, as the auditor’s report is one of the important documents that support users’ decisions. The research sample was a group of auditors working in auditing companies and offices, as questionnaire forms were distributed to them to survey their opinions. The researchers reached a set of conclusions, the most important of which is that the extended report prepared according to brainstorming sessions is an integrated document of quality due to the balanced and understandable information it contains that covers users’ need for information and increases their confidence. The extended report increases the quality and informative value of the report; as additional disclosures help users directly or indirectly to evaluate the financial status of the economic unit being audited. The researchers reached a set of recommendations, the most important of which is that auditors should use brainstorming sessions to prepare the extended report according to the International Auditing Standard ISA700 and other standards related to preparing the extended report. The Council of the Auditing and Control Profession in Iraq should oblige auditing companies and offices to adhere to the report. Expanded reporting standards and other relevant standards.